2014
DOI: 10.1002/ceat.201300766
|View full text |Cite
|
Sign up to set email alerts
|

Unpromoted and Mn‐Promoted Cobalt Catalyst Supported on Carbon Nanotubes for Fischer‐Tropsch Synthesis

Abstract: Langmuir‐Hinselwood (LH) and power rate equations were applied to describe the kinetics of the Fischer‐Tropsch reaction on cobalt catalysts and manganese‐doped cobalt catalysts supported on carbon nanotubes (CNTs). LH‐based kinetics characterize the activity behavior of the unpromoted Co/CNT system satisfactorily, but fail with respect to the manganese‐promoted Co/CNT catalyst. An alternative LH equation is able to fit the experimental data, but the fitting parameters are out of the range of usual values and u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…From an engineering and industrial point of view, it is important to establish kinetic rate equations integrating the performance and the scale-up of the process e.g., reactor modeling and process modeling [59]. Kinetic rate equations are most of the time described by empirical power law models based on Langmuir-Hinshelwood-type equations [60].…”
Section: Reaction Mechanismsmentioning
confidence: 99%
See 3 more Smart Citations
“…From an engineering and industrial point of view, it is important to establish kinetic rate equations integrating the performance and the scale-up of the process e.g., reactor modeling and process modeling [59]. Kinetic rate equations are most of the time described by empirical power law models based on Langmuir-Hinshelwood-type equations [60].…”
Section: Reaction Mechanismsmentioning
confidence: 99%
“…Based on the power law model, they concluded that CO is strongly adsorbed dissociatively on the catalyst surface, and the reaction rate is significantly influenced by the partial pressure of H2. In another study, Rose et al [59] used Langmuir-Hinshelwood and power rate equations (Eq.5) to describe the kinetics of FTS reaction on cobalt catalysts and manganese-doped cobalt catalysts supported on CNTox. This study was carried out in a wide range of pressure and temperature, since the FTS activity and selectivity strongly depend on the syngas pressure and temperature.…”
Section: Reaction Mechanismsmentioning
confidence: 99%
See 2 more Smart Citations
“…Langmuir-Hinshelwood (LH) and power rate equations were applied to describe the kinetics of the FT reaction on cobalt catalysts and manganese-doped cobalt catalysts supported on CNTs. 190 LH-based kinetics characterize the activity behavior of the unpromoted Co/CNT system satisfactorily, but fail with respect to the Mn-promoted Co/CNT catalyst. An extensive study of FTS on CNT supported and γ-alumina-supported cobalt catalysts with different amounts of cobalt was reported.…”
Section: Fischer-tropsch Synthesismentioning
confidence: 96%